QTL mapping of flowering time in Brassica napus: a study on the interplay between temperature and day length after vernalization - Heinrich, Eva; Schierholt, Antje; Möllers, Christian (Frontiers in Plant Science, 2025)
Flowering is a critical life stage for plants, and the regulation of flowering is heavily influenced by environmental factors and is genetically very complex. In oilseed rape (Brassica napus L.), a major oil crop, yield is heavily dependent on successful flowering. Until now, the influences of day length and temperature on flowering time have mostly been studied in spring-type rape, although they also affect flowering in winter oilseed rape after vernalization, and changing climate conditions alter springtime temperatures. In this study, a doubled haploid population derived from a cross between a winter and a spring-type oilseed rape was examined for the effect of cool and warm temperatures (11°C and 22°C) in combination with long and short days (8/16-h light) on flowering time after vernalization. Quantitative trait locus (QTL) analysis revealed major QTLs for flowering time in two homologous regions on chromosomes C06 and A07, which were found to interact epistatically. It was found that temperature can either delay or promote flowering depending on day length and genotype, highlighting the complex interplay between these factors. Our study provides new insights into the genetic basis of flowering time regulation in B. napus, especially after vernalization, and highlights the importance of considering the interplay between temperature and day length in breeding programs for this crop, particularly in the context of climate change.